Comparative Analysis of Pressure Reconstruction Methods from Simulation Impulse Data - Кочкарьов, Владислав; Мартинюк, Петро (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This thesis investigates the ill-posed problem of reconstructing the pressure time profile p(t) on a structure from discrete impulse data obtained in a 2D Discrete Element Method (DEM) simulation of blast loading. A systematic comparative analysis of six reconstruction methods is carried out: interval averaging, trapezoidal rule inversion, direct differentiation of cumulative impulse, cubic spline approximation, Savitzky-Golay filtering, and Tikhonov regularization with a non-negativity constraint. To assess the quality and physical adequacy of the solutions, a comprehensive system of metrics was developed, including smoothness, integral conservation (energy balance), and the fraction of non-physical negative values. For comparison with experimental data, a robust procedure is proposed that includes automatic time scale calibration and scale-independent signal shape validation. All results presented in the article are generated automatically within a single computational pipeline. The analysis shows that direct differentiation methods are critically unstable, while the Tikhonov regularization method with automatic parameter selection via Generalized Cross-Validation demonstrates the best trade-off between stability, smoothness, and fidelity to the source data. — У цих тезах досліджується некоректна задача реконструкції часової залежності тиску p(t) на споруді за дискретними даними імпульсу, отриманими в 2D-симуляції повітряного вибуху методом дискретних елементів (DEM). Проведено систематичний порівняльний аналіз шести методів реконструкції: інтервального усереднення, обернення за правилом трапецій, прямого диференціювання кумулятивного імпульсу, кубічної сплайнової апроксимації, фільтрації Савицького-Ґолея та регуляризації Тихонова з обмеженням по невід’ємності. Для оцінювання якості та фізичної коректності розв’язків розроблено комплексну систему метрик, що включає гладкість, інтегральне збереження (енергетичний баланс) і частку нефізичних від’ємних значень. Для порівняння з експериментальними даними запропоновано надійну процедуру, яка включає автоматичне калібрування часової шкали та перевірку форми сигналу, незалежну від масштабу. Усі результати, наведені в роботі, генеруються автоматично в межах єдиного обчислювального конвеєра. Аналіз показує, що методи прямого диференціювання є критично нестійкими, тоді як метод регуляризації Тихонова з автоматичним вибором параметра за допомогою узагальненої крос-валідації демонструє найкращий компроміс між стійкістю, гладкістю та точністю відтворення вихідних даних.